2020
DOI: 10.1021/acsomega.9b04231
|View full text |Cite|
|
Sign up to set email alerts
|

Physicochemical Properties of Terebic Acid, MBTCA, Diaterpenylic Acid Acetate, and Pinanediol as Relevant α-Pinene Oxidation Products

Abstract: The physicochemical properties and the synthesis of four α-pinene oxidation products, terebic acid, 3-methyl-1,2,3-butanetricarboxylic acid (MBTCA), diaterpenylic acid acetate (DTAA), and pinanediol, are presented in this study. The physicochemical properties encompass thermal properties, solubility in water, and dissociation constant (pK a ) for the investigated compounds. It was found that terebic acid exhibits a relatively high melting temperature of 449.29 K, whereas pinanediol revealed a low melting tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Consequently, the temperature at which the first peak appeared is referred to as the melting temperature ( T m ). In this study, the T m values for 3-MBTCA, terpenylic acid, DTAA, and 1,2,4-B3CA were found to be 136.1, 81.3, 110.6, and 219.7 °C, respectively, which were comparable to previously reported ranges: 144–149.6, 92–94, 121.1, and 229–231 °C, respectively. ,− In heat flow profiles of 3-MBTCA, DTAA, and 1,2,4,5-B4CA, two endothermic peaks were found in addition to the last peak, at which the sample vaporized completely. For the case of 3-MBTCA, DTAA, and 1,2,4,5-B4CA, the first endothermic peaks were found at 30.4, 111.7, and 58.1 °C, respectively, with a slight decrease in mass as evident in the corresponding TGA thermograms.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Consequently, the temperature at which the first peak appeared is referred to as the melting temperature ( T m ). In this study, the T m values for 3-MBTCA, terpenylic acid, DTAA, and 1,2,4-B3CA were found to be 136.1, 81.3, 110.6, and 219.7 °C, respectively, which were comparable to previously reported ranges: 144–149.6, 92–94, 121.1, and 229–231 °C, respectively. ,− In heat flow profiles of 3-MBTCA, DTAA, and 1,2,4,5-B4CA, two endothermic peaks were found in addition to the last peak, at which the sample vaporized completely. For the case of 3-MBTCA, DTAA, and 1,2,4,5-B4CA, the first endothermic peaks were found at 30.4, 111.7, and 58.1 °C, respectively, with a slight decrease in mass as evident in the corresponding TGA thermograms.…”
Section: Resultssupporting
confidence: 86%
“…TGA and DSC recorded the change in mass and the difference in energy supplied to reference and sample pans as a function of the temperature. DSC is a well-established technique to analyze the phase transition processes such as melting point, crystallization, and decomposition of chemical species. , DSC analysis was utilized to determine the melting temperatures ( T m ) of the aforementioned chemical species. In each analysis, two aluminum pans were utilized.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…MBTCA (3-methyl-1,2,3-butanetricarboxylic acid, 99% purity) and cis -pinic acid (99.5% purity) were synthesized in our laboratory, as described previously. , α-Pinene (>99% purity), cis -pinonic acid (98% purity), dimethyl sulfoxide (DMSO, MolBio-Grade), Dulbecco’s phosphate-buffered saline (PBS), methanol (ChromaSolv-Grade), and 0.1% acetic acid were purchased from Sigma-Aldrich (Merck, Poland). High-purity methanol (optima LC/MS grade) was purchased from Fisher Chemical (U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…The contribution of SOA to the Earth’s solar radiative budget, climate change, and cloud formation, as well as its impact on human health through gas- and aqueous-phase processes, have been progressively investigated. Still, however, the vast fraction of potentially important SOA sources and transformation processes remain unknown. ,, Hydrophilic aerosol particles serve as Cloud Condensation Nuclei (CCN) and promote cloud formation playing a significant role in cooling the Earth’s climate . Among biogenic VOCs (BVOCs), isoprene and monoterpenes have already gained ample attention, while green leaf volatiles (GLVs), also potentially precursors of SOA, have been much less studied.…”
Section: Introductionmentioning
confidence: 99%